Role of the Competitiveness among the Variables Determining the Situation of Agricultural Industry in Russia’s Regions: Results of the Factor Analysis - Elena Vasilyevna Zhiryaeva; Maria Nikolaevna Dmitrieva (Управленческое консультирование)
The article examines the competitiveness of agriculture of the Russian Federation through the indicators of its regional development. Based on results of the Pearson correlation calculation was established that competitiveness of agriculture is closely tied with a small amount of factors. Among factorial conditions high correlation is observed with the investments into fixed capital (0.7), to a lesser extent - with the capital of other sort (a cattle livestock), also land resources and a labor force. Also demand conditions matter, namely: trade turnover of the agricultural organizations (0.73). At the same time dependence upon the state aid is expressed not so clearly: correlation is average, being at the level of 0.5-0.6 depending on a type of subsidies. There were found 14 groups of factors as a result of the factorial analysis. Three among factors had importance: crop production condition; livestock production condition; degree of openness of the region. Values of these factors were calculated for parent population’s objects. The most common situation is when the subject of the Russian Federation had a high value on one of three factors, but insignificant on two others. Subjects of the Russian Federation with low value of competitiveness have negative values of all factors as well, with rare exceptions. Moscow, the Krasnodar area, the Belgorod region have unique values of variables. A certain trend between factors wasn’t detected - all three factors are independent between each other. The conclusion is drawn that the competitiveness increases mainly due to the development of livestock production.